Flexible Approximation Functions: Resonant Loads - G. A. Filippovich; M. A. Yantsevich (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Patch antennas have found wide application in UAVs due to their numerous useful properties. However, since such an antenna system is essentially a resonator, the problem of its matching remains unresolved. The existing publications mostly deal with specific cases and report the typical values of the matching band of 5–7 %, which cannot be considered sufficient when there is a need to use the signal spectrum of up to hundreds of MHz. Therefore, research aimed at using more efficient methods of broadband matching could be of interest for engineers.   Aim. To develop a broadband matching technique based on the generalized Darlington synthesis method using flexible approximating functions (AF) for load models with resonant properties.   Materials and methods. The capabilities of the generalized Darlington synthesis method are extended AFs with increased variation properties. Flexible control of AF weight coefficients makes it possible to realize both smooth and wave frequency characteristics. The method is analytical and does not use iterative procedures. The mathematical apparatus of the method is based on an analysis of deductions in the zeros of the load resistance transfer function.   Results. Flexible approximating functions were established to be effective for synthesis of matching circuits with resonant properties. Solutions for matching the loads with multiple transfer zeros both at the origin and in infinity were obtained. The opportunity of creating patch antennas with a matching layer up to 40 % and more was demonstrated.   Conclusion. The results obtained for the SWR of patch antennas show that the potential estimates of matching limits are available only for analytical methods.